Fossils of the Carpathian region - Főzy, István (Life of the past., 2013)
This book provides a comprehensive review of the fossil record of the Carpathian Basin. The book describes and illustrates the region's fossils, recounts their history, and tells the stories of key people involved in paleontological research in the area. In addition to covering the important fossils of this region, special attention is given to rare finds and complete skeletons. The region's fossils range from tiny foraminifera to the Transylvanian dinosaurs, mastodons, and mammals. The book also gives nonspecialists the opportunity to gain a basic understanding of paleontology. Sidebars present brief biographies of important figures and explain how to collect, prepare, and interpret fossils.